Medical surgical nursing : assessment and management of clinical problems - Lewis, Sharon Mantik (Elsevier/Mosby, 2011)
Offers coverage of the various trends, topics, and clinical developments in medical-surgical nursing, to help you provide care in health care environment. This title explores patient care in various clinical settings and focuses on key topics such as prioritization, clinical decision-making, patient safety, and NCLEX[registered] exam preparation